Effect of SIM on Knowledge and Practice Regarding Bio-Medical Waste Management Among Lab Technicians (International Journal of Scientific Research in Science and Technology, 2024)
A study to evaluate the Effectiveness of Self-instructional Module on Knowledge and Practice Regarding Biomedical Waste Management among Lab Technicians was under taken at Ferozpur. A pre experimental one group pre-test post-test research design was carried out to determine the knowledge and practice. The study was conducted in selected laboratories at Ferozpur, 50 lab technicians from selected laboratories of Ferozpur who met the inclusion criteria was selected for the study using a Non Probability sampling – convenient sampling technique. Structured knowledge questionnaire and practice check list about biomedical waste management was used to assess the knowledge and practice of the Lab technicians. The structured knowledge questionnaire and practice check list along with objectives and blue print was validated by ten experts. Split – Half method was used to find out the reliability of the tool. The reliability co- efficient of knowledge questionnaire was found to be r= 0.90 and for practice check list it was found to be r 0.79. The subject’s knowledge and practice regarding biomedical waste management was assessed on the 1st day. Same day SIM was administered. On the 7th day a post-test was carried out for the same set of lab technicians. The findings revealed that the findings using modified gain suggested that the post-test scores in all areas were higher than the pre-test scores. There was no significant association between pretest knowledge level of lab technicians and the selected factors–age, years of experience and participation in in-service education programme. There was no significant association between the pre test knowledge and practice score with selected variables such as age, gender, religion, educational qualification, designation and experience on biomedical waste management.